BS ISO 13007-6. Ceramic tiles. Grouts and adhesives. Part 6. Requirements, test methods, evaluation of conformity, classification and designation for waterproof membranes used with the installation of ceramic tiles (9th December 2019) - British Standards Institution,
No abstract available